Virtual and Augmented Reality: A New Approach to Aid Users of Myoelectric Prostheses - Soares, Alcimar Barbosa; Júnior, Edgard Afonso Lamounier; Andrade, Adriano de Oliveira; Cardoso, Alexandre (IntechOpen, 2012)
None